Conservation networks do not match the ecological requirements of amphibians - Matutini, Florence; Baudry, Jacques; Fortin, Marie-Josee; Pain, Guillaume; Pithon, Josephine (Peer Community Journal, 2023)

(untitled)
Amphibians are among the most threatened taxa as they are highly sensitive to habitat degradation and fragmentation. They are considered as model species to evaluate habitats quality in agricultural landscapes. In France, all amphibian species have a protected status requiring recovery plans for their conservation. Conservation networks combining protected areas and green infrastructure can help the maintenance of their habitats while favouring their movement in fragmented landscapes such as farmlands. Yet, assessing the effectiveness of conservation networks is challenging. Here, we compared the ecological requirements of amphibian species with existing conservation network coverage in a human-dominated region of western France. First, we mapped suitable habitat distributions for nine species of amphibian with varying ecological requirements and mobility. Second, we used stacking species distribution modelling (SSDM) to produce multi-species habitat suitability maps. Then, to identify spatial continuity in suitable habitats at the regional scale, we defined species and multi-species core habitats to perform a connectivity analysis using Circuitscape theory. Finally, we compared different suitability maps with existing conservation networks to assess conservation coverage and efficiency. We highlighted a mismatch between the most suitable amphibian habitats at the regional scale and the conservation network, both for common species and for species of high conservation concern. We also found two bottlenecks between areas of suitable habitat which might be crucial for population movements induced by global change, especially for species associated with hedgerow mosaic landscapes. These bottlenecks were not covered by any form of protection and are located in an intensive farmland context. Synthesis and applications - We advocate the need to better integrate agricultural landscape mosaics into species conservation planning as well as to protect and promote agroecological practices suitable for biodiversity, including mixed and extensive livestock farming. We also emphasize the importance of interacting landscape elements of green infrastructure for amphibian conservation and the need for these to be effectively considered in land-use planning policies.